Aspirin versus placebo in pregnancies at high risk for preterm pre-eclampsia. (June 2018) - Story, Lisa; Nelson-Piercy, Catherine
A recent multicentre placebo-controlled trial by Rolnick et al. has indicated that taking 150 mg aspirin daily in women at high risk of pre-eclampsia reduced the incidence of the disease from 4.3% to 1.5% in comparison with placebo. Although the findings of this study are important, a high proportion of women withdrew their consent and not all safety outcomes have been reported. This journal watch article discusses the paper in more detail.